Analysis of ecological environment quality heterogeneity across different landform types in Myanmar and its driving forces - Shuangfu Shi; Shuangyun Peng; Zhiqiang Lin; Ziyi Zhu; Dongling Ma; Yuanyuan Yin; Xiangmei Lu; Ting Li; Luping Gong (Ecological Indicators)
Ecological Environmental Quality (EEQ) assessment is a crucial method for understanding regional ecological conditions and identifying ecological problems. Understanding how EEQ responds to various natural and anthropogenic factors under different landform conditions is extremely important to improve the accuracy and usefulness of the assessment. Landforms, as a key natural geographic element, influence not only the spatial distribution of EEQ, but also the nature and intensity of human activities. However, we lack a comprehensive understanding of how different landform types affect the ecological environment. In this paper, we quantitatively assessed the spatial heterogeneity characteristics of EEQ in Myanmar based on the Remote Sensing Ecological Index (RSEI) model, and used Geodetector to reveal the driving mechanisms of EEQ in terms of the whole region and specific landform types. The results showed that: (1) The overall EEQ in Myanmar showed a fluctuating downward trend from 2000 to 2020, and the spatial heterogeneity is obvious. The plains and hills had poor EEQ, while the mountains, highlands and most of the northern regions have better EEQ. (2) The EEQ of different landform types differed significantly. The EEQ was best in middle relief mountains and poorer in plains and high relief mountains. (3) Land use, human footprint and net primary productivity (NPP) were the main factors affecting EEQ in Myanmar, and there are significant spatial and temporal dynamic interactions between different factors. (4) There were significant differences in the factors affecting EEQ between landform types. For example, EEQ in plains, hills, low relief mountains, and middle relief mountains was influenced by a combination of natural and anthropogenic factors. In contrast, upland mountain areas were mainly influenced by natural factors alone. As the degree of landform fluctuation increases, the influence of each factor generally showed a downward trend. This study reveals the spatio-temporal variation characteristics of Myanmar’s EEQ, key driving factors, and differential response mechanisms of ecological environment evolution under different landform types, and provides a scientific basis for formulating ecosystem protection and restoration strategies based on local conditions.